Failure of dental implants in cemento-osseous dysplasia: a critical analysis of a case - OLIVEIRA,Maiolino Thomaz Fonseca (2014)
Introduction: Osseointegrated dental implants have been routinely used in oral rehabilitation. Patients with dysplastic bone diseases represent a particular challenge for oral rehabilitation with dental implants. Nevertheless, the installation of implants in patients with cemento-osseous dysplasia (COD) has been reported with apparent success.Objective: In this paper, we present a case of a patient with COD in which a dental implant had been installed and lost six months later. In this regard, we analyzed pertinent aspects of the indications for dental implants in patients with COD considering the pathogenesis, dysplastic nature, and behavior of the disease.Conclusion:The present case report illustrates that COD can be considered a limiting factor in the recommendation for a dental implant. Because of this, it is imperative to inform the patient about the risks of surgically manipulating the diseased bone.